Bundo Kanduang dan Tantangan Politik Dalam Badan Perwakilan Anak Nagari (BPAN) - Irawati, Irawati (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2010)
The structure of Nagari governance has provided space for ‘Bundo Kanduang’ participation in decision-making. Bundo kanduang become a compulsory element in the membership of the Badan Perwakilan Anak Nagari (BPAN). This means that women in Minangkabau have been given the opportunity legally to engage in public decision-making. However, in formal legitimacy they are not guaranteed to play a role as bundo kanduang representatives. In fact, Bundo Kanduang still faces cultural challenges, internal and religion in BPAN. Kata Kunci: Bundo Kanduang, Diskriminasi, Tantangan Politik, Partisipasi, Minangkabau, BPAN